2020
DOI: 10.3390/met10091214
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Model of 30CrMoA Steel with Strain Correction

Abstract: It is necessary to establish a constitutive model of 30CrMoA steel to optimize the forming shape and mechanical properties of high-speed train axles. The experimental stress–strain curve of 30CrMoA steel was obtained by an isothermal compression test on a Gleeble-3500 thermal simulation test machine under temperature of 1273~1423 K and strain rate of 0.01~10 s−1. Considering the effect of strain on the material constant, an empirical constitutive model was proposed with strain correction for 30CrMoA steel. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the full-scale physical fatigue tests, the axle successfully passed the tests, and under the condition of a speed of 350 km/h, the safety factor was around 1.99, which significantly improved the safety level. Due to the similar chemical composition with 30NiCrMoV12, 30CrMoA has been developed to replace the 30NiCrMoV12 because of the cheaper manufacturing cost and the promising properties that has been shown in the previous study [28]. The chemical composition of 30CrMoA steel is shown in Table 1.…”
Section: Materials Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…In the full-scale physical fatigue tests, the axle successfully passed the tests, and under the condition of a speed of 350 km/h, the safety factor was around 1.99, which significantly improved the safety level. Due to the similar chemical composition with 30NiCrMoV12, 30CrMoA has been developed to replace the 30NiCrMoV12 because of the cheaper manufacturing cost and the promising properties that has been shown in the previous study [28]. The chemical composition of 30CrMoA steel is shown in Table 1.…”
Section: Materials Modelmentioning
confidence: 97%
“…Constitutive relations of 30CrMoA steel are obtained and imported into the material bank of finite element software. The material models are described in the previous studies [28,29], and are shown in Eqs. ( 5) and ( 6).…”
Section: Materials Modelmentioning
confidence: 99%
“…The material of the HSCWT is 30CrMoA steel. The material model of the HSCWT is shown in Equation (1) [29,30]. The finite element model of the three-roll skew rolling HSCWT is established in Simufact Forming V14.0 software.…”
Section: Finite Element Model Of Hscwt For Three-roll Skew Rollingmentioning
confidence: 99%
“…As can be seen from figure 2, the finite element model is composed of a roll, a push block, a positioning ring, a baffle, a plug and a billet, wherein the billet size is Φ 45mm × 200mm, and in order to simulate the Mannesmann effect in real production [13], a small hole with a diameter of 2mm is opened in the center of the billet, and the material is set to 30CrMoA. Its rheological curve is shown in figure 3, and the empirical constitutive equation is [14][15]:…”
Section: Figure 2 Finite Element Model Of Processmentioning
confidence: 99%